GPR182 is a broadly scavenging atypical chemokine receptor influencing T-independent immunity - Melgrati, Serena; Gerken, Oliver J.; Artinger, Marc; Radice, Egle; Szpakowska, Martyna; Chevigné, Andy; D’Uonnolo, Giulia; Antonello, Paola; Thelen, Sylvia; Pelczar, Pawel; Legler, Daniel F.; Thelen, Marcus (Frontiers in Immunology, 2023)
Immune responses highly depend on the effective trafficking of immune cells into and within secondary lymphoid organs (SLOs). Atypical chemokine receptors (ACKRs) scavenge chemokines to eliminate them from the extracellular space, thereby generating gradients that guide leukocytes. In contrast to canonical chemokine receptors, ACKRs do not induce classical intracellular signaling that results in cell migration. Recently, the closest relative of ACKR3, GPR182, has been partially deorphanized as a potential novel ACKR. We confirm and extend previous studies by identifying further ligands that classify GPR182 as a broadly scavenging chemokine receptor. We validate the "atypical" nature of the receptor, wherein canonical Gprotein-dependent intracellular signaling is not activated following ligand stimulation. However, βarrestins are required for ligand-independent internalization and chemokine scavenging whereas the C-terminus is in part dispensable. In the absence of GPR182 in vivo, we observed elevated chemokine levels in the serum but also in SLO interstitium. We also reveal that CXCL13 and CCL28, which do not bind any other ACKR, are bound and efficiently scavenged by GPR182.Moreover, we found a cooperative relationship between GPR182 and ACKR3 in regulating serum CXCL12 levels, and between GPR182 and ACKR4 in controlling CCL20 levels. Furthermore, we unveil a new phenotype in GPR182-KO mice, in which we observed a reduced marginal zone (MZ), both in size and in cellularity, and thus in the T-independent antibody response. Taken together, we and others have unveiled a novel, broadly scavenging chemokine receptor, which we propose should be named ACKR5.